PENGARUH GAJI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. CHANG SHIN REKSA JAYA - Nurrahman, Herlin; Yusuf, Ramayani (LPPM Politeknik Pajajaran ICB, 2023)
The phenomenon that occurs in companies is a decrease in work productivity. A salary level that is still very low will affect efforts to increase employee productivity, on the contrary, a very low level of productivity is difficult to guarantee an increase in salary. Salary issues in the company PT. Chang Shin Reksa Jaya is employee dissatisfaction with the salary he receives from the company. This study aims to examine how much influence Salary has on Work Productivity at PT. Chang Shin Mutual Jaya. This study used quantitative methods, with a population of 12,000 and an equal sample of 100 respondents using non-probability sampling techniques by distributing questionnaires. Data analysis used simple regression and correlation tests. The results obtained in this study show that there is a positive and significant influence of Salary on Work Productivity at PT. Chang Shin Reksa Jaya, it can be assumed that salary is very influential on Work Productivity.